Effects of multiple climate change stressors: ocean acidification interacts with warming, hyposalinity, and low food supply on the larvae of the brooding flat oyster Ostrea angasi - Cole, V J; Parker, L M; O’Connor, S J; O’Connor, W A; Scanes, E; Byrne, M; Ross, P M (Marine Biology, 2016)
Ocean acidification, rising temperatures, and increased intensity of rain events are occurring due to climate change. Individually, each of these stressors has the potential to influence the growth and survival of many marine organisms, particularly during early development. Together the interactive and multiple impacts of elevated pCO2, temperature, and salinity may be exacerbated by a lack of food. Life history traits are important in determining the response of organisms to climate change. Larvae that develop within a brood chamber, such as the flat oyster, Ostrea angasi, may be pre-exposed to living a higher CO2 environment. This study determined the pH of the fluid surrounding the gills of adult oysters where larvae are brooded and investigated the interactive effects of the multiple climate-related stressors: ocean acidification, warming, hyposalinity, and reduced food availability, on development of O. angasi larvae. The fluid surrounding the larvae was of pH 7.88 ± 0.04, lower than that of surrounding sea water, and was significantly reduced (to pH 7.46 ± 0.05) when oysters remained closed as occurs in nature during periods of stress caused by low salinity. Elevated pCO2 [853–1194 µatm (pHNBS 7.79)] resulted in larvae being 3 % smaller, but it had no effect on the timing of progression through developmental stages, percentage of abnormalities, or survival of larvae. Exposure to elevated pCO2 together with increased temperature (+4 °C) or reduced salinity (20) had a negative effect on the time to the eyed larval stage and with an increase in the percentage of abnormal larvae. Unexpectedly, larvae did not meet their higher metabolic requirements to survive under elevated pCO2 by eating more. In a sublethal effect of elevated pCO2, larval feeding was impaired. We found that O. angasi larva were relatively resilient to elevated pCO2, a trait that may be due to the acclimatisation of hypercapnic conditions in the brood cavity or because they are released from the brood cavity at an older, possibly less sensitive stage. This result contrasts with the larvae of broadcast spawning oysters which are extremely sensitive to elevated pCO2. © 2016, Springer-Verlag Berlin Heidelberg.